Laboratory Testing Methods for Novel Severe Acute Respiratory Syndrome-Coronavirus-2 (SARS-CoV-2) - D'Cruz, Roshan J.; Currier, Arthur W.; Sampson, Valerie B. (Frontiers in Cell and Developmental Biology, 2020)
Following the first reports of coronavirus disease-19 (COVID-19) by China to the World Health Organization (WHO) on 31st December 2019, more than 1,119,794 novel severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) cases have been reported by authorities in 204 countries and territories by 4th April 2020. The outbreak and spread of COVID-19 worldwide, highlights the critical need for developing rapid and reliable diagnostic testing methods for emerging human coronavirus (CoV) infections. Testing is crucial to track the spread of disease during a pandemic, and to swiftly permit public health interventions including isolation, quarantine, and appropriate clinical management of afflicted individuals. The key components of viral diagnostic tests are (1) collection of the appropriate sample (blood, nasal swab, throat swab), (2) availability of the genetic and proteomic sequences of the novel virus for analysis and (3) rapid and accurate laboratory testing methods. The current gold standard for the molecular diagnosis of SARS-CoV-2 infection is the real-time reverse transcriptase-polymerase chain reaction (RT-PCR) for the qualitative and quantitative detection of viral nucleic acids. Other relevant laboratory methods include enzyme-linked immunoassays (EIA) for viral antibody and antigen detection, and serum viral neutralization (SVN) assays for antibody neutralization determination. The challenges faced in developing a diagnostic test for a novel pathogen are the ability to measure low viral loads for early detection, to provide low or no cross-reactivity with other viral strains and to deliver results rapidly. Several point-of-care molecular devices are currently being integrated for fast and accurate diagnosis of SARS-CoV-2 infections. This review discusses the current laboratory methods available to test for coronaviruses by focusing on the present COVID-19 outbreak.